The hidden impacts of micro/nanoplastics on soil, crop and human health - Russo, Mariateresa; Oliva, Mariateresa; Hussain, M. Iftikhar; Muscolo, Adele (Journal of agriculture and food research, 2023)
This review examines the growing concerns surrounding the ubiquitous prevalence of micro/nanoplastic pollution and the possible dangers and consequences on the global environment. While the environmental effects have been extensively studied, the extent of potential human health hazards and effects remains largely unexplored. This overview aims to shed light on the connection between plastics, human well-being and environment to extend current knowledge on this subject. The review covers the status of global micro/nanoplastics pollution, and the risks they present to human health encompass harmful chemical elements, contaminant carriers, and physical harm. Several key findings emerged: (1) Microplastics in the soil adhered to crop seeds and root surfaces or accumulated within their vascular systems, leading to the obstruction of water and nutrient uptake; (2) micro/nanoplastics induce oxidative damage to plants disrupting their metabolic processes; (3) Chemical additives released from microplastics triggered cytotoxic and genotoxic effects in plants; (4) Microplastics altered the biotic and abiotic conditions of the soil, thereby affecting the availability of water and nutrients to crops; and finally, (5) The combined toxicity of different microplastics in soil can have adverse effects on plants. In conclusion, this review sheds light on the repercussions of soil microplastics on plants and advocates, for further research to better understand their impact on the natural environment and human well-being.